포인트 클라우드 분류를 위한 이웃 연결성 합성곱 신경망 - 이진원 (The Graduate School, Ajou University, 2019)
포인트 클라우드는 3차원 스캔에서 기본 데이터 구조로써, 많은 분야에서 활용되고 있다. 포인트 클라우드를 활용하기 위해 예전부터 SIFT (Scale Invariant Feature Transform)나 HOG (Histogram of Gradient) 와 같은 사용자정의 특징에 관한 다양한 연구를 했지만 일정 수준의 정확도를 넘지 못했다. 또한, 포인트 클라우드의 불규칙적이고 무질서한 특징 때문에 이미지 분류에서 우수한 성능을 보인 CNN (Convolutional Neural Network)의 적용이 쉽지 않았다. 본 논문에서는 이웃 연결성과 밀접 연결성을 활용한 DenX-Conv를 제안한다. 이웃 연결성은 들로네 삼각 분할을 활용하여 기하학적 위상수학 관계가 높은 점을 찾아 군집했으며, 밀집 연결성은 깊은 네트워크를 구축하여 군집된 점의 특징을 깊은 레이어까지 잘 전달될 수 있도록 했다. 그 결과 Mod-elNet40 분류 테스트에서 다른 논문들에 비해 우수한 92.5%의 정확도를 보였으며, 적은 점의 개수에서도 강건한 성능을 나타냈다. Point clouds are a basic data structure in 3D scanning and are used in many fields. To utilize point clouds, they have done various studies on handcrafted features such as SIFT (Scale Invariant Feature Transform) and HOG (Histogram of Gradient) but have not achieved good accuracy. Because of the irregular and unordered of the point cloud, it was not easy to apply CNN, which has shown excellent performance in image classification. In this paper, we propose DenX-Conv neighbor connectivity and dense connectivity. Neighborhood connectivity has been exploited to find high geometric topological relationships by using the Delaunay Triangulation, and dense connectivity has built up a deep network so that the feature of clustered points can be conveyed well to deep layers. As a result, it showed 92.5% accuracy in ModelNet40 classification test, which is superior to other papers, and it showed robust performance even in a small number of points.
학위논문(박사)--아주대학교 일반대학원 :산업공학과,2019. 8